PENGARUH PRODUK DOMESTIK BRUTO (PDB), INFLASI DAN KURS RUPIAH TERHADAP YIELD SUKUK NEGARA SR 009 PERIODE 2017-2020 - Kamila, Dwi Yusti; Tripalupi, Ramadhani Irma; Afifah, Eva (Likuid Jurnal Ekonomi Industri Halal, 2021)
The sale and purchase of Islamic bonds or sukuk products in the secondary market is more volatile, the profit which is the reference for investors in the secondary market is generally yield to maturity (YTM) or often called yield. According to Laily Fitriyah et al. in their research, the economic conditions in a country can be an important reference for investors' decisions in that country, this is in line with the theory pioneered by Rosel in 1963, namely the Arbitrage Pricing Theory that bond yields can be influenced by macroeconomic factors. Gross Domestic Product (GDP), inflation and the rupiah exchange rate are some branches of macroeconomics that can describe the economic condition of a country. This study uses the Vector Error Correction Model (VECM) data analysis method. The data processing tools used are Eviews9 and Microsoft Excel 2019 to support initial data processing. The VECM estimation results show that in the short term only the rupiah exchange rate variable has a significant negative effect on the yield of SR09, GDP has an insignificant negative effect and inflation has an insignificant positive effect on the yield of SR009. Meanwhile, in the long term, all independent variables have a significant negative effect on the yield of SR009.Keywords: GDP, Inflation, Rupiah Exchange, Yield.